Earthquake, Tsunami and Liquefaction in the City of Palu: Efforts to Enhance the Sustainability of SMEs in the Future - Indah Lestari; Muhammad Ikbal Abdullah; Andi Chairil Furqan (University of Merdeka Malang, 2023)
This study aims to identify and analyze the impact of disasters on the financial performance of micro, small, and medium enterprises (MSMEs), as well as to analyze the differences in financial performance of MSMEs before and after disasters based on their business type and sector. The study was conducted in the city of Palu, with a sample of 1,504 MSMEs affected by earthquakes, tsunamis, and liquefaction. The research findings indicate that natural disasters have a negative impact on the financial performance of MSMEs in Palu. This means that the earthquakes, tsunamis, and liquefaction that occurred in Palu and its surrounding areas in 2018 resulted in a decline in the financial performance of MSMEs in the city, across industrial, service, and trade sectors. Additionally, this study provides new insights to the local government, highlighting the need to encourage MSMEs to develop disaster risk mitigation strategies, particularly to maintain financial stability in the aftermath of natural disasters.